2014
DOI: 10.12693/aphyspola.126.380
|View full text |Cite
|
Sign up to set email alerts
|

Chirality Induced by Magnetoelectrolysis

Abstract: Surface chiral formation of Cu lms was investigated in the galvanostatic electrodeposition under a magnetic eld of 5 T perpendicular to the electrode surface. The surface chirality was examined by electrochemical voltammograms of a chiral molecule of tartaric acid. The chiral induction depended on the magnetoelectrodeposition time, and this implied that the formation of the self-organized state of magnetohydrodynamic ows around the electrode is crucial for the chiral formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…11,12 Furthermore, a well-regulated local convection may produce a chiral aggregation of achiral molecules, or induce any chirality in the reaction products conducted in a capillary, as suggested at the rotated liquid-liquid interface, 37 in the electrode surface under a magnetic field, 38 and under the application of rotational and magnetic forces. 39 …”
Section: Discussionmentioning
confidence: 99%
“…11,12 Furthermore, a well-regulated local convection may produce a chiral aggregation of achiral molecules, or induce any chirality in the reaction products conducted in a capillary, as suggested at the rotated liquid-liquid interface, 37 in the electrode surface under a magnetic field, 38 and under the application of rotational and magnetic forces. 39 …”
Section: Discussionmentioning
confidence: 99%
“…21A). 259 The enantiomeric excess (ee) ratio in the voltammograms, which is defined as ee = ( i l p − i d p )/( i l p + i d p ), where i l p and i d p represent the peak currents of l - and d -TA, respectively, gave positive values during 30–50 s deposition time (with a maximum value of 0.5 at 40 s), where the steady self-organized state of the MHD flows formed on the surface of the Cu film electrode. These facts implied that the self-organized state of the micro-MHD and the vertical MHD flows are crucial for the formation of chiral Cu film surfaces (Fig.…”
Section: Application Of Electromagnetic Forcementioning
confidence: 99%
“…21B). 259 Furthermore, they found that the specific adsorption of chloride ions on the film surfaces and the direction of the magnetic field of 5 T had a drastic influence on the chiral property of the Cu film, which was measured by the voltammetric ee ratio of l - and d -alanine. They suggested that not only the micro-MHD vortices but also the rate-limiting steps of Cu dislocation are responsible for the chiral surface formation.…”
Section: Application Of Electromagnetic Forcementioning
confidence: 99%